1992
DOI: 10.1128/mcb.12.1.379
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cell death is a dominant phenotype: triggering of activation-driven T-cell death independent of the T-cell antigen receptor complex.

Abstract: The failure of Thy-1 and Ly-6 to trigger interleukin-2 production in the absence of surface T-cell antigen receptor complex (TCR) expression has been interpreted to suggest that functional signalling via these phosphatidylinositol-linked alternative activation molecules is dependent on the TCR. We find, in contrast, that stimulation of T cells via Thy-1 or Ly-6 in the absence of TCR expression does trigger a biological response, the cell suicide process of activation-driven cell death. Activation-driven cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1993
1993
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…However, functional differences have already been documented between T cell hybridoma and the BW5147 parental cells. For instance, BW5147 fails to undergo activation-driven cell death in response to stimulation viaThy-1 or Ly-6 whereasT cell hybridomas resulting from the fusion of BW5147 and of a matureTcel1 do [32]. In the latter instance the parental mature Tcells may have provided factor(s) that confer susceptibility to activationdriven cell death.…”
Section: Ek-positive Cells) the Results Reported In Figs 3 Andmentioning
confidence: 94%
“…However, functional differences have already been documented between T cell hybridoma and the BW5147 parental cells. For instance, BW5147 fails to undergo activation-driven cell death in response to stimulation viaThy-1 or Ly-6 whereasT cell hybridomas resulting from the fusion of BW5147 and of a matureTcel1 do [32]. In the latter instance the parental mature Tcells may have provided factor(s) that confer susceptibility to activationdriven cell death.…”
Section: Ek-positive Cells) the Results Reported In Figs 3 Andmentioning
confidence: 94%
“…Apart from an inhibition experiment in comple ment-deprived rats [4], it was shown that nephritis could be worsened in rats treated with antibodies against mem brane inhibitors of complement [S. Matsuo et al, pers. commun], Anti-Thy-1 mAb has been found to induce activation-driven cell death in transformed T cell hybridoma and non-transformed T cell lines [22,23], as well as apoptosis in Thy-l-positive thymocytes [13], Thus, both forms of cell death may coexist in the initial injury. Fur ther investigation is necessary to clarify the roles of each form of cell death in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mAb directed at GPIanchored molecules, such as Thy-1 and Ly-6, are capable of activating mature T cells to proliferate in a manner similar to antigen-or anti-TCIL/CD3 mAb-driven T cell activation (33). The same stimuli have also been found to elicit T hybridoma or nontransformed T cell death (47,48). This ADCD is of apoptotic nature and can be prevented by RNA and protein synthesis inhibitors, and the two compounds EGTA and cyclosporin A (47)(48)(49).…”
Section: Thy-l-mediated Apoptosis Is Not Inhibited By Rna or Protein mentioning
confidence: 99%